A Longer Running Internal Combustion Engine Using Simple Motif in Lubrication System Taking into Account Heat Reduction and Increased Performance - Dr. Mohammad M. Al-Azzawi; Muayyad A.H Al-Hayali (MUSURGIA, 2020)
Most important aspect of machine and auto life would be the proper lubrication, well-oiled automobile will outlast maintained poorly models by many years. No different when it comes to Industrial machinery, save a lot of money and hassle in the future if a good lubrication system is introduced [1]. Moving machine parts are accomplished by lubricating systems which introduce oil, grease and other lubricants to them. Reduced friction between parts by means of lubricants, Longevity is increased [1]. Without lubrication, most machines would overheat or suffer extreme damage [2]. Anyone who has ever neglected to keep their car oiled knows first-hand just how extensive this damage can be. Cooling and lubricating systems are the fundamentals part of almost all internal combustion engines that work in conjunction with each other promoting sustainable engine performance. Hence, lubricating systems are integral part of any engine system that contribute in heat reduction during operation, less heat guarantees longer life engine components. In this research a simple motif in lubrication system will make significant improvement in i.c. engine system.